PENGARUH PENYALURAN KREDIT CEPAT AMAN (KCA) DAN PENJUALAN LOGAM MULIA TERHADAP PROFITABILITAS PADA PT.PEGADAIAN CABANG PINRANG - Nurfadillah (Journal AK-99, 2021)
Abstract This research aims to find out the study of the dominant and simultaneous influence between Capat Aman Credit Products (KCA) and Noble Products on the Profitability or capability of PT. Pawnshop (Persero) Pinrang Branch in generating Profit during 2015 to 2017. The data collection techniques used in this study are documentation and interviews. The data analysis techniques in this study used multiple linear regression analyses. The results showed that safe fast credit (KCA) and precious metals sales had a significant impact on profitability by 92% and the remaining 8% was influenced by other variables not mentioned in this study, namely Creation products and other Products. Where the variable contributes to the output value or contributes to the Profitability of PT. Pawnshop (Persero) Pinrang Branch. More dominant variables affect pt profitability. Pawnshop (Persero) pinrang branch is a secure fast credit (KCA) contributing as much as 88.5%.